Peran Guru dalam Penanganan dan Pencegahan Perilaku Bullying di Kelas V MI Al Mujahidah Tajurhalang Bogor - Ernawati; Chaira Saidah Yusrie; Dhini Sesi Yarrini; Diana; Satmah Rahmai Noviyanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research was conducted to assessthe role of the teacher in handling and preventing bullying at fifth-grade Madrasah Ibtidaiyah. The descriptive qualitative method with interviews, observation, and documentation as a technique to collect the data. The subject criteria were the principal and the teachers who taught in fifth grade. The data analyzed using data reduction, presentation, and inductive data analysis.The result of this research shows that bullying occurs in MI AL MUJAHIDAH in verbal and physical bullying form. The role of teachers to prevent the bullying showed in several ways, such as a group of classical guidance, implementing coachingactivities at the beginning and the end of the semester, as well as increasing religious activities in the school environment in order to increase students faith in Allah SWTand familiarize children with good moral habits or akhlakulkarimahbehavior in deeds and words. teachers will also work together with parents to advise the students about bullying. Teacher will provide the parents about bullying danger, so they could evaluate their children.